Perancangan Tata Letak Fasilitas Gudang Produk Jadi menggunakan Metode Activity Relationship Diagram Pada PT JVC Electronics Indonesia - Felix Yohannes Panjaitan; Fahriza Nurul Azizah (Peneliti.net, 2022)
PT JVC Electronics Indonesia (PT JEIN) is a large company engaged in the electronics industry, especially in the car audio section. In doing the design, this research uses the ARC and ARD methods. Based on the results obtained, it can be seen that the current layout condition is considered to be less than optimal because, in the design process and the placement of attributes in the warehouse, they are not in sync and transportation is hampered. The proposal for improving the warehouse layout at the company is obtained by placing the components of the warehouse based on the level of importance and frequency of products going in and out of the warehouse. It was identified that Asian, European, and American products were the products that experienced the most frequent in and out of the warehouse. Therefore, the three products are placed in a place that is easily accessible during transportation. While the other two products, namely Japanese and local products, were placed in another position, namely on the side of the warehouse. The layout change aims to increase the effectiveness of the movement of goods and reduce the occurrence of product variance.